2016
DOI: 10.3390/su8020186
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and the Change of Fertilizer Use Intensity for Agricultural Production in Henan Province

Abstract: China's urbanization has resulted in significant changes in agricultural land use. However, understanding of the linkages between urbanization and fertilizer use intensity is limited. Using county-level panel data for Henan Province, 1995Province, -2008 and panel econometric models, we investigate the impact of urbanization and other socioeconomic factors on fertilizer use intensity, with a focus on the two key processes related to urbanization-shrinking agricultural land area and increasing urban wages. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Urban land use continued to increase, while agricultural land development slowed. Therefore, increasing the intensity of fertilizer application became a universal way to ensure food security [ 49 , 50 ]. However, the contribution of these two effects decreased, which indicated that the growth rate of fertilizer application decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Urban land use continued to increase, while agricultural land development slowed. Therefore, increasing the intensity of fertilizer application became a universal way to ensure food security [ 49 , 50 ]. However, the contribution of these two effects decreased, which indicated that the growth rate of fertilizer application decreased.…”
Section: Resultsmentioning
confidence: 99%
“…According to the latest statistics, the total carbon emissions in Henan Province increased by more than 25% from 2006 to 2015 [ 24 ]. Many studies have measured the fate of carbon emissions caused by LUCC in Henan province [ 9 , 23 , 24 , 25 ], but these tend to focus on carbon emissions within an administrative region at provincial, municipal or county level. This has left the analysis of carbon emission effects caused by LUCC along natural boundaries (such as basin boundaries) generally understudied.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the methods of characterizing agricultural land use intensity, research showed that: (i) a new system has been constructed using farm accounting network data that include land use, socio-economic factors, local climate, and government subsidies to calculate the unit land cost input [ 4 ]; (ii) Polynomial regression models have been applied to detect the spatial distribution of agricultural intensity in France in order to provide an important reference for the implementation of related agricultural policies [ 5 ]; and (iii) Some scholars still use indicators of the inputs or outputs to measure agricultural intensification based on traditional agricultural statistics. Indicators of inputs include fertilizers, intercropping levels [ 6 , 7 ], nitrogen input (for arable land and permanent grassland), livestock unit density and pesticide amounts (herbicide, insecticide, and flame-retardant herbicide and insecticide) [ 8 , 9 ], while indicators of the outputs include cereal and animal husbandry products [ 10 ], which have only been applied to analyze the characteristics of agricultural land use and their informative significance, rather than focusing on the innovation of characterization methods [ 11 , 12 , 13 ]. Despite the development of remote sensing science, few scholars have used remote sensing images to characterize agricultural land use intensity dynamically and in real time [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%